Optimization of High-density Culture Process of Lacticaseibacillus paracasei Lp.R3 - Shihui FANG; Yao XIONG; Zhao ZHANG; Junfang LIN; Tao CHEN; Liqiong GUO (Shipin gongye ke-ji)
Lacticaseibacillus paracasei Lp.R3 is a probiotic strain with excellent functions. In order to realize its industrial application, high-density cultivation was carried out to increase the number of viable bacteria, the effects of medium composition, static culture conditions, and fermentation tank processes on the number of viable Lp.R3 bacteria were investigated by single factor experiments and orthogonal experiments optimization. The best result (4.75×109 CFU/mL of viable bacteria number) was achieved when Lp.R3 cultured in the medium supplemented with 30 g/L glucose, 50 g/L yeast extract, 10 g/L anhydrous sodium acetate, 0.1 g/L manganese sulfate, and 1 g/L Tween80 under the culture conditions of 1% inoculation level, pH7 and 35 ℃, which was 2.91 times greater than that cultured in MRS medium. In terms of the production in 5 L fermentation tanks, the best result (2.56×1010 CFU/mL of viable bacteria number) was given when L.p R3 fermented under constant pH of 5 neutralized by 25% ammonia, continuous variable feed of 75 g/L glucose, and agitation without aeration, which was 15.51 times greater than that cultured in MRS medium. In summary, the high-density production protocol of Lp.R3 was optimized in present study, providing a promising guide to accomplish large-scale production of Lp.R3.